Analisis Pengaruh Koneksi Politik Dan Corporate Governance Terhadap Pengungkapan Corporate Social Responsibility (CSR) Industri Perbankan Indonesia - Azza Mahandani Wardah; Putri Nugrahaningsih (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2020)
Disclosure of sustainability reports is increasingly intensified by the government, one of which is through regulations listed in OJK Number 51/POJK.03/2017 concerning Implementation of Financial Sustainability of Financial Services Institutions, Issuers, and Public Companies, must report the sustainability of the report separately. The concept initiated by Elkington in 1988, Triple Bottom Line (TBL)-contained three pillars to assess the success of a company in terms of economic, environmental, and social (people, planet, and profit). Established on the Global Reporting Initiative G4 (GRI-G4) indicators consisting of 91 items and GRI-Standards Global Reporting Initiative Indicators. Sample selection with purposive sampling shows 33 financial statements from 11 banking sector companies in 2016 until 2018. In terms of political connection of the board of commissioners and directors as well as government ownership and also foreign ownership variables do not affect the disclosure of corporate social responsibility in the Indonesian banking industry. Disclosure of corporate social responsibility has been negatively affected by the independent commissioner variable. Managerial ownership proves that these variables have a positive effect on disclosure of corporate social responsibility. The foreign ownership variable indicates that there is no influence, which means foreign capital ownership is not influenced by corporate social responsibility, especially in the banking industry in Indonesia. According to the results of statistical tests, the size of the company assets does not affect the disclosure of corporate social responsibility, especially in the banking industry in Indonesia.